2022
DOI: 10.1016/j.ejmp.2022.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center planning study of radiosurgery for intracranial metastases through Automation (MC-PRIMA) by crowdsourcing prior web-based plan challenge study

Abstract: Background: Planning radiosurgery to multiple intracranial metastases is complex and shows large variability in dosimetric quality among planners and treatment planning systems (TPS). This project aimed to determine whether autoplanning using the Muliple Brain Mets (AutoMBM) software can improve plan quality and reduce inter-planner variability by crowdsourcing results from prior international planning study. Methods: Twenty-four institutions autoplanned with AutoMBM on a five metastases case from a prior inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…For the six UK centers that participated both in the MC-PRIMA and RTTQA studies [1,5], we found that there was a drastic improvement of the planning e ciency by autoplanning. For this studied case of ve metastases, 610 minutes (or 10.2 hours) would have been saved if it had been planned using AutoMBM.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…For the six UK centers that participated both in the MC-PRIMA and RTTQA studies [1,5], we found that there was a drastic improvement of the planning e ciency by autoplanning. For this studied case of ve metastases, 610 minutes (or 10.2 hours) would have been saved if it had been planned using AutoMBM.…”
Section: Discussionmentioning
confidence: 88%
“…The study case was originally from the Local-HER-0 trial protocol [6] and was used in a prior international planning competition hosted by the ProKnow 1 system. Details of this study case was described in [5,7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid gray area indicates 0 difference ± the 95% reproducibility limits in volume-averaged CI or GI from a multicenter planning study. 7
Figure 4 Plot of the differences in the volume of normal brain local to each metastasis receiving 12 Gy (local V12 Gy) for each planning target volume (PTV) between the clinical plan and the automatic plans with clinical starting tables (blue markers, left) and generic starting tables (green markers, right). Differences are shown as a function of PTV volume.
…”
Section: Resultsmentioning
confidence: 99%